2017
DOI: 10.5539/ijef.v9n11p35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exchange Rate Returns on Equity Prices: Evidence from South Africa and Nigeria

Abstract: This paper examines the exchange rate returns of the Rand (relative to the US dollar) and the Naira (relative to the US dollar) for the presence of volatility. It also examines the effect of the exchange rate returns on the performance of their respective stock market. While it was found that the returns of the South African Rand was volatile, the Nigerian naira was not. Estimating the effect of exchange rate returns and crude oil price on the stock market indices of both countries showed that exchange rate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Using a VAR model to explain the link between prices of crude oil and investments in renewable energy in African states, Tambari and Failler, (2020) found that oil price shocks had a positive and statistically significant impact on African countries' investments in renewable energy. Daggash and Abraham (2017) discovered an identical phenomenon using the VAR Granger Causality Method.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Using a VAR model to explain the link between prices of crude oil and investments in renewable energy in African states, Tambari and Failler, (2020) found that oil price shocks had a positive and statistically significant impact on African countries' investments in renewable energy. Daggash and Abraham (2017) discovered an identical phenomenon using the VAR Granger Causality Method.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In addition, the study reveals a long run equilibrating connection existing amongst the variables. Daggash and Abraham (2017) analyze the exchange rate returns effect on equity prices in Nigeria and South Africa and checked for the presence of volatility in the Naira and the Rand using the Vector Autoregressive (VAR) model. The study finds the existence of volatility in the returns of the Rand, while such does not exist in the Naira return.…”
Section: Literature Reviewmentioning
confidence: 99%